Core of sensory gating deficits in first-episode schizophrenia: attention dysfunction - Ding, Yushen; Tian, Qing; Hou, Wenpeng; Chen, Zhenzhu; Mao, Zhen; Bo, Qijing; Dong, Fang; Wang, Chuanyue (Frontiers in Psychiatry, 2023)
Background: Sensory gating deficits in schizophrenia can indicate higher-order psychopathological impairment, and the introduction of prepulse inhibition (PPI) of subjective attention may more aptly indicate this defect. Therefore, this paper highlights the association between modified PPI and cognitive function by introducing subjective attention components. Methods: Fifty four patients with unmedicated first-episode schizophrenia (UMFE) and 53 healthy controls were enrolled. Evaluations were carried out using the modified Prepulse Inhibition paradigm, which comprises Perceived spatial separation PPI (PSSPPI) and Perceived spatial colocation PPI (PSCPPI). Cognition was examined for all subjects using the Chinese version of the MATRICS Consensus Cognitive Suite Test (MCCB). Results: Overall composite MCCB score, speed of processing, attention/ vigilance, working memory, verbal learning, visual learning, and reasoning and problem-solving domain scores were considerably lower in UMFE than in healthy controls, with statistically significant differences (t = −4.74 to −2.08, all P < 0.05). The PSSPPI in UMFE was markedly deficient in both (ISI = 60 ms and 120 ms) than healthy controls (t = −3.77 and −3.61, both P < 0.01). Correlations indicated that PSSPPI 60 ms was negatively linked to total PANSS scores (r = −0.27, P < 0.05), and PSSPPI 60 ms was positively linked to the speed of processing, attention/ vigilance, and social cognition (all r = 0.27, P < 0.05). Additional multiple linear regression analysis, after controlling for the effects of gender, age, years of education, and smoking, demonstrated that PSSPPI 60 ms still had a major effect on attentional alertness (β = 0.23, P = 0.02) and social cognition (β = 0.23, P = 0.04). Conclusions: UMFE had significant sensory gating deficits and cognitive deficits, which were more aptly indicated by the PSSPPI; the PSSPPI 60 ms of the UMFE related to clinical symptoms and cognitive function, indicating that the PSSPPI may demonstrate psychopathological symptoms linked to psychosis.